What primary school teachers say about their beliefs on teaching and learning of English as a Second Language (ESL) - Hamidah Yamat,; Kulwant Kaur Kartar Singh, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The belief system upheld by a teacher largely controls and shapes his or her views and practices of the subject matter and pedagogical content knowledge. Whether or not this applies to an English as a Second Language (ESL) context underpinned the purpose of the study presented and discussed in this paper. This Case Study aimed to explore three purposively selected rural primary school teachers’ beliefs and practices about teaching and learning of English. They each had fifteen, six and one year of experience; respectively. Data was gathered through individual interviews and triangulated with observations and document analysis. Themes were identified through constant comparative and thematic analysis and assisted with the use of CAQDAS, Atlas Ti version 7; a software for analyzing qualitative data. Findings indicate that despite the different number of years of experience, the teachers’ beliefs had an impact on how they felt English should be taught and therefore employed pedagogical strategies they believed would work for their students. This implies there is a need to for sharing good practice which will enable even novice teachers to get the pedagogical content knowledge which are tested through real teaching experiences.